2020
DOI: 10.1016/j.isci.2020.101815
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Plant Breeding as a Response to the Complexity of Climate Change

Abstract: Summary Climate change is one of the processes that have already overstepped the safe planetary boundaries, together with the rate of biodiversity loss and human interference with the nitrogen and phosphorus cycles. The three processes are related to agriculture and, as such, to both food safety and food security, and ultimately to human health. Adaptation to climate change is a difficult breeding objective because of its complexity, its unpredictability, and its location specificity. However, one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 90 publications
0
46
1
Order By: Relevance
“…A challenge for plant genetic resource managers and breeders is to anticipate target phenotypes for crop improvement. Increased pest, pathogen, and weed pressures, temperature and rainfall fluctuations, drought, salinization of soils, and human encroachment of agricultural lands are all seen as impending threats to crop production (Ceccarelli and Grando, 2020). Whatever breeding strategies are used, the understanding of natural genetic variation and its partitioning remains crucial for success (Ebert, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A challenge for plant genetic resource managers and breeders is to anticipate target phenotypes for crop improvement. Increased pest, pathogen, and weed pressures, temperature and rainfall fluctuations, drought, salinization of soils, and human encroachment of agricultural lands are all seen as impending threats to crop production (Ceccarelli and Grando, 2020). Whatever breeding strategies are used, the understanding of natural genetic variation and its partitioning remains crucial for success (Ebert, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, given the evolutionary potential of weeds as enhanced under climate change, an "evolutionary plant breeding" approach could be developed [147], both to counter evolutionary advances of weeds and incorporate the lessons weeds have taught us. The close evolutionary relationship between crops and weeds should facilitate this approach [37].…”
Section: Management Implicationsmentioning
confidence: 99%
“…The recognition that heterogeneous populations, such as evolutionary populations (EP) and mixtures, constitute the ideal genetic materials for a breeding strategy addressing heterogeneous TPE, is particularly important today as a way of coping with the extraordinary complexity of climate change (Ceccarelli and Grando, 2020). Evolutionary populations (also known as Composite Cross Populations or Bulk Populations) are obtained by mixing the seed obtained from the crossing of a number of varieties, while mixtures are obtained by mixing the seed of a number of varieties (Wolfe and Ceccarelli, 2020).…”
Section: The Strategymentioning
confidence: 99%
“…Evolutionary populations (also known as Composite Cross Populations or Bulk Populations) are obtained by mixing the seed obtained from the crossing of a number of varieties, while mixtures are obtained by mixing the seed of a number of varieties (Wolfe and Ceccarelli, 2020). Ceccarelli and Grando (2020) have shown that climate change is a complex breeding objective because:…”
Section: The Strategymentioning
confidence: 99%
See 1 more Smart Citation